Indonesia’s Hedging Strategy in The US–China Rivalry in The Indo-Pacific - Nasution, Muhammad Haekal; Windy Dermawan (Universitas Komputer Indonesia, 2025)
This study analyzes Indonesia’s position in the Indo-Pacific amid intensifying US-China Rivalry, focusing on how it preserves its national interests and strategic flexibility. Using a qualitative approach based on secondary data such as official foreign policy statements, government documents, and academic literature the research examines how Indonesian Foreign Policy responds to structural pressures in the region. The findings show that Indonesia does not align rigidly with either the United States or China. Instead, it adopts a hedging strategy that maintains constructive relations with both powers while avoiding formal alignment. This approach reflects Indonesia’s long-standing principle of being “free and active,” enabling it to navigate geopolitical competition without compromising its Strategic Autonomy. The study argues that Indonesia’s behavior is shaped by both the evolving power structure of the Indo-Pacific and its normative foreign policy foundations. By balancing engagement and caution, Indonesia sustains diplomatic flexibility and reduces the risk of entrapment in great-power rivalry. Ultimately, the research highlights how Indonesia manages external pressures while safeguarding autonomy, demonstrating the adaptive character of its foreign policy strategy in a contested regional order. Keywords— Indonesia, Indo-Pacific, Indonesian Foreign Policy, Strategic Autonomy, US-China Rivalry